Uji Aktivitas Antibakteri Ekstrak Etanol Daun Andong Merah terhadap Eschericia coli dan Staphylococcus aureus - Reca Indiyen; Fika Aryati; Angga Cipta Narsa (Proceeding of Mulawarman Pharmaceuticals Conferences, 2020)
Infection disease is one of the most common diseases in the world. Infection can be caused by bacteria Escherichia coli and Staphylococcus aureus which are now resistant to some antibiotics, so new agents are needed to overcome antibiotic resistance. Red andong leaves are empirically efficacious for treating wounds, hemorrhoids, inflammation, diarrhea and stopping bleeding (hemostasis). This study aims to determine the yield of ethanol extracts red andong leaves and determine the antibacterial activity of ethanol extracts of red andong leaves against Escherichia coli and Staphylococcus aureus. The research began with the process of extracting red andong leaves by maceration method, then carried out antibacterial testing by the well diffusion method. The results showed the extract concentrations of 10%, 30%, and 50% were able to inhibit the growth of Escherichia coli and Staphylococcus aureus. The biggest antibacterial activity of red andong extract was obtained at a concentration of 50% with a inhibition zone of 17,836 mm (Staphylococcus aureus) and 9,012 mm (Escherichia coli).